Critical industries in the time of Asia-Pacific geopolitics: Lessons for the Philippines - Deryk Matthew N. Baladjay; Jean Clarisse T. Carlos (Philippine Institute for Development Studies (PIDS), 2024)
This study examines the interplay between Asia-Pacific geopolitics and the Philippines' critical industries, focusing on telecommunications, energy, mining, and digital infrastructure. Utilizing a Philippine-centric lens, it explores how geopolitical tensions, particularly between the U.S. and China, influence industry-specific vulnerabilities and value chains. Drawing from qualitative data, including key informant interviews across APEC economies, the research highlights the strategic importance of multilateral cooperation, trade diversification, and policy harmonization within APEC. It integrates World-Systems Theory to analyze the systemic impacts of geopolitical dynamics and proposes actionable strategies for bolstering industry resilience while aligning with regional and global development goals.
Keywords: 330; critical industries; geopolitics; Asia-Pacific; APEC